Discourse in a modern Arctic: can we supplant sovereignty? – commentary to Pawliw, Berthold and Lasserre - Carleton, Alexandra (Fennia - International Journal of Geography, 2021)
In this reflection I contemplate on the nature of claiming sovereignty over the Arctic through the political discourse, as used in the Harper administration. I question the mobilization of discourses to substantiate claims and lasting jurisdiction over the Arctic as the true nature of reconstructing narratives. In particular, whether the truer questions are how and why we seek sovereignty over areas of wilderness and why discourse is needed at all to legitimise the goodness of such claiming.